Identification Of The Community's Need For Emergency Nursing Services During A Pandemic - Yulia Candra Lestari; Luluk Nurani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2022)
ABSTRACT The Covid-19 pandemic has had an impact on emergency nursing services, this is shown by the decline in the number of visits to the emergency department. This is caused by several internal and external factors. Emergency nursing services during a pandemic need to be optimized because they play a role in saving lives and reducing mortality and morbidity rates. The purpose of this study was to explore the community's need for emergency nursing services during the covid 19 pandemic. The research design was qualitative with in-depth interview data collection methods on 6 participants. The sample was selected according to the inclusion criteria, namely people who can speak Indonesian properly and correctly and people who have experienced emergency conditions during the pandemic. Researchers as the main instrument in the study and interview guides as a reference for questions. The results of the interviews will be written in the form of transcripts and then analyzed using thematic analysis methods to obtain research themes. From the results of data analysis obtained 2 research themes. The first theme is the need to strengthen trust regarding the safety, convenience and efficiency of services, the second is an integrated service from the nearest and advanced health facilities. Optimizing emergency nursing services during a pandemic is important to improve by taking into account the needs of the community, this is done so that people can feel safe and comfortable in accessing emergency nursing services so that emergency events can be handled properly. Keywords: Nursing, emergency department, emergency department, service optimization, phenomenology